2009
DOI: 10.1007/s12274-009-9078-8
|View full text |Cite
|
Sign up to set email alerts
|

Milestones in molecular dynamics simulations of single-walled carbon nanotube formation: A brief critical review

Abstract: We present a brief review of the most important efforts aimed at simulating single-walled carbon nanotube (SWNT) nucleation and growth processes using molecular dynamics (MD) techniques reported in the literature. MD simulations allow the spatio-temporal movement of atoms during nonequilibrium growth to be followed. Thus, it is hoped that a successful MD simulation of the entire SWNT formation process will assist in the design of chirality-speciÀ c SWNT synthesis techniques. We give special consideration to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 66 publications
1
51
0
Order By: Relevance
“…Once the electronic forces are evaluated, the atomic trajectories are evaluated by conventional force integration. Interested readers may refer to a critical review of the SWNT 152 for an elementary understanding of the various forms of MD approaches to simulating nanotubes.…”
Section: Nanotubesmentioning
confidence: 99%
“…Once the electronic forces are evaluated, the atomic trajectories are evaluated by conventional force integration. Interested readers may refer to a critical review of the SWNT 152 for an elementary understanding of the various forms of MD approaches to simulating nanotubes.…”
Section: Nanotubesmentioning
confidence: 99%
“…In particular, below 600 K, carbondiffusion on the catalyst surface limits the growth, but at higher temperature, the growth fully depends on cap liftoff. Irle et al [41] presented a brief review of MD simulations of SWCNT formation, which mainly focused on the role of metal catalyst particles in the process. They concluded that the use of a quantum potential is essential for a qualitatively correct description of the catalytic behavior of the metal cluster.…”
Section: Discrete Computational Modelingmentioning
confidence: 99%
“…Irle et al [41] suggested that although it is computationally expensive, the use of quantum potential is essential for the qualitatively correct description of the catalyst behavior of metal clusters. Borjesson and Bolton [42] used first-principles based DFT calculations to study the effect of nickel carbide catalyst composition on nanotube growth.…”
Section: Discrete Modelsmentioning
confidence: 99%
“…A tip growth mechanism was demonstrated by Charlier et al [119]. Actual growth and elongation of a SWNT on a small metallic particle was achieved using DFTB simulations by Ohta et al [120,121].…”
Section: Detailed Atomistic Simulations Of Nanostructure Growth Procementioning
confidence: 99%